PENGARUH PEMAHAMAN PERPAJAKAN, KESADARAN WAJIB PAJAK DAN PENURUNAN TARIF PAJAK PP NO 23 TAHUN 2018 TERHADAP KEPATUHAN WAJIB PAJAK (STUDI EMPIRIS UMKM MAKANAN DAN MINUMAN DI LUBUK PAKAM) - Wulandari, Riska; Jayusman, Sri Fitria; Wibowo, Muhammad Rizaldy; Wirananda, Henny Andriyani (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to analyze the influence of tax understanding, taxpayer awareness, and tax rate reductions based on Government Regulation No. 23 of 2018 on taxpayer compliance of MSMEs in the food and beverage sector in Lubuk Pakam. The research method used is a quantitative approach with data collection techniques through questionnaires. The research sample consisted of 70 respondents who were MSMEs in the food and beverage sector in Lubuk Pakam. Data analysis was conducted using multiple linear regression analysis with SPSS software, including validity tests, reliability tests, classical assumption tests, and hypothesis tests (t-test, F-test, and coefficient of determination). The results show that tax understanding, taxpayer awareness, and tax rate reductions based on Government Regulation No. 23 of 2018 have a positive and significant effect on taxpayer compliance. These findings indicate that increasing tax understanding and taxpayer awareness, as well as the implementation of tax rate reduction policies, can encourage taxpayer compliance levels of MSMEs in the food and beverage sector in Lubuk Pakam. This study provides encouragement for the tax authorities to continue improving tax education and optimizing the implementation of tax rate policies that support MSME growth.